Small R&D Performers in Canada - Antoine Rose; Fred Gault (Foresight and STI Governance)
The small performers, whose costs for R&D are less than 100 thousand dollars per year, consist more than half of total organisations involved in R&D in Canada. This vast segment includes companies of all sizes (both in number of employees and amount of income), and employs seven percent of all personnel performing R&D. But at the same time, the share of small performers makes only two percent of total expenditure on R&D in the Canadian private sector.